2007
DOI: 10.1016/j.brainres.2007.02.054
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of discourse context and world knowledge in online sentence comprehension. Evidence from the N400

Abstract: In an ERP experiment we investigated how the recruitment and integration of world knowledge information relate to the integration of information within a current discourse context. Participants were presented with short discourse contexts which were followed by a sentence that contained a critical word that was correct or incorrect based on general world knowledge and the supporting discourse context, or was more or less acceptable based on the combination of general world knowledge and the specific local disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
4
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 20 publications
10
108
4
3
Order By: Relevance
“…The immediate impact of propositional truth-value in counterfactual sentences about unrealistic worlds, as reported here, contrasts with several reports in the literature that pitted contextual relevance with real-world truth-value (e.g., Hald et al, 2007) or real-world possibility (e.g., Warren et al, 2008). As noted in the Introduction, these other reports may have involved a context that rendered an impossible consequence mildly congruent, yet still less predictable or plausible than a possible consequence.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The immediate impact of propositional truth-value in counterfactual sentences about unrealistic worlds, as reported here, contrasts with several reports in the literature that pitted contextual relevance with real-world truth-value (e.g., Hald et al, 2007) or real-world possibility (e.g., Warren et al, 2008). As noted in the Introduction, these other reports may have involved a context that rendered an impossible consequence mildly congruent, yet still less predictable or plausible than a possible consequence.…”
Section: Discussioncontrasting
confidence: 99%
“…Whereas several studies have reported that contextual relevance outweighs real-world constraints from an early moment on (e.g., a cartoon-like story about an amorous peanut can invert the relative ease of processing ''the peanut was salted'' as compared to ''the peanut in love'', Nieuwland & Van Berkum, 2006; see also Filik, 2008;Filik & Leuthold, 2008), some results on the processing of literally false or unrealistic sentences suggest that context does not completely overrule briefly disruptive effects of local violations (e.g., Hald, Steenbeek-Planting, & Hagoort, 2007;Warren, McConnell, & Rayner, 2008). For example, Warren et al reported that despite a fantasy-context (e.g., Harry Potter practicing magic spells on food items), words that incurred semantic violations (e.g., 'bread' in ''Harry used a book to teach the tough bread'') elicited longer fixations and gaze durations than in unproblematic sentences (e.g., ''Harry used a microwave to heat the tough bread'').…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, studies that aim to elucidate the interplay between linguistic experience and world knowledge do exist. Hald, Steenbeek-Planting & Hagoort (2007), for example, contrasted stereotypical and nonstereotypical sentences (e.g., "The city Venice has very many canals/roundabouts [. .…”
Section: Interplay Between Linguistic Experience and World Knowledgementioning
confidence: 99%
“…In sentence processing, the amplitude of this effect is modulated by the cloze probability of the anomalous word, with more improbable words yielding larger N400 effects and with semantic priming reducing the size of these effects (Kutas and Hillyard 1984). Other sources of contextual information (e. g., discourse context, world knowledge, attitudes) also modulate N400 size (e. g., Hald et al 2007;Nieuwland and Van Berkum 2006). The N400 has also been portrayed as a reflection of the effortful retrieval of conceptual information from long-term semantic memory (e. g., Kutas and Federmeier 2000).…”
Section: Event-related Potentials and L2 Proficiencymentioning
confidence: 99%